Nanoelectromechanical digital logic circuits using curved cantilever switches with amorphous-carbon-coated contacts. (November 2015) - Ayala, Christopher L.; Grogg, Daniel; Bazigos, Antonios; Bleiker, Simon J.; Fernandez-Bolaños, Montserrat; Niklaus, Frank; Hagleitner, Christoph
Abstract: Nanoelectromechanical (NEM) switches have the potential to complement or replace traditional CMOS transistors in the area of ultra-low-power digital electronics. This paper reports the demonstration of prototype circuits including the first 3-stage ring oscillator built using cell-level digital logic elements based on curved NEM switches. The ring oscillator core occupies an area of 30 μm × 10 μm using 6 NEM switches. Each NEM switch device has a footprint of 5 μm × 3 μm, an air gap of 60 μm and is coated with amorphous carbon (a-C) for reliable operation. The ring oscillator operates at a frequency of 6.7 MHz, and confirms the simulated inverter propagation delay of 25 ns. The successful fabrication and measurement of this demonstrator are key milestones on the way towards an optimized, scaled technology with sub-nanosecond switching times, lower operating voltages and VLSI implementation.